Improved dynamic correction method in seismic analysis of both classically and non-classically damped structures. - D'Aveni, Antonino (Earthquake engineering & structural dynamics.)
A step bystep approximate procedure taking into consideration high frequency modes, usually neglected in the modal analysis of both classically and non-classical damped structures, is presented. This procedure can be considered as an extension of traditional modal correction methods, like the mode acceleration method and the dynamic correction method, which are very effective for structural systems subjected to forcing functions described by analytical laws. The proposed procedure, herein called improved dynamic correlation method, requires two steps. In the first step, the number of differential equations of motion are reduced and consequently solved by using the first few undamped mode shapes. In the second step, the errors due to modal truncation are reduced by correcting the dynamic response and solving a new set of differential equations, formally similar to the original differential equations of motion. The difference between the two groups of differential equations lies in the forcing vector, which is evaluated in such a way as to correct the effects of modal truncation on applied loads.